The effect of implant and abutment diameter on peri-implant bone stress: A three-dimensional finite element analysis - Helen Mary Abraham; Jacob Mathew Philip; Ashish R Jain; C J Venkatakrishnan (Wolters Kluwer Medknow Publications, 2016)
Introduction: Load transfer mechanisms from the implant to surrounding bone and failure of osseointegrated implants are affected by implant geometry and mechanical properties of the site of placement as well as crestal bone resorption. Estimation of such effects allows for a correct design of implant geometry to minimize crestal bone loss and implant failure. Objectives: To evaluate the effect of implant and abutment diameter on stress distribution in the peri-implant area. Materials and Methods: Three-dimensional finite element models created to replicate completely osseointegrated endosseous titanium implants and were used for the purpose of stress analysis. Two study groups that consisting of a regular platform (RP) group and narrow platform (NP) group were used with a standard bone density and loaded using the ANSYS Workbench software to calculate the von Mises and Principal (maximum tensile and minimum compressive) stress. Results: The von Mises, compressive, and tensile stresses in the peri-implant bone were lower in the RP model compared to the NP model. Conclusion: RP model yielded a positive result with regard to lowering of peri-implant bone stress levels, in healthy as well as compromised bone qualities when compared to NP designs.